Pendampingan Lesson Study Untuk Meningkatkan Kompetensi Guru Sekolah Dasar di KKG Gugus Sungai Miai Banjarmasin dalam Menerapkan Pendekatan Saintifik Menggunakan Kurikulum 2013 - Dessy Noor Ariani (Publikasi Pendidikan, 2018)
The purpose of this community service activity is to provide an applicable understanding to classroom teachers in KKG SD Gugus Sungai Miai about a scientific approach. This approach is relevant to curriculum 2013. Based on various research results that scientific approach can be used to improve the quality of learning. The implementation of this community service activity is using the stages of lesson study, namely: Planning (planning of learning), Do (implementation and observation of learning), and See (reflection of learning).